Penerapan Bootstrap Financing : Sebuah Tinjauan Teoritis - Tommy C. Efrata; Christian Herdinata (BIP's JURNAL BISNIS PERSPEKTIF, 2013)
Bootstrap financing methods commonly used as an alternative to access a capital, since the conventional access of capitalis limited for small and medium firms in Indonesia.This study aims to explain the application of bootstrap financing for small and medium-sized firms in getting access to capital. Subjects used in this study are 67 owners of small and medium firms in Surabaya. The method used is descriptive qualitative. The results of this study indicate that for the method loan from the owner, instrument using personal credit card is the most frequent one. On the other hand, for the method funding from family, borrowing from family and friends is the most common instrument.